ANALISIS FAKTOR PENYEBAB ANAK PUTUS SEKOLAH JENJANG SEKOLAH MENENGAH PERTAMA DI DESA MAJU KARYA KECAMATAN PARINDU KABUPATEN SANGGAU - Pandu, Kristian Trikurnianto; Aminuyati, Aminuyati; Atmaja, Thomy Sastra (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study describes the causes of students at the junior high school level in Desa Maju Karya, Kecamatan Parindu of Kabupaten Sanggau, drop out of school. This study identifies the factors causing children in the studied area to drop out of school. This study analyzes the factors that cause children to drop out of school in Maju Karya Village, Parindu District, Sanggau Regency. Qualitative approach with a descriptive method was employed in this study. The research data was obtained using observation, interviews, and documentation. Data reduction, data display, and drawing conclusions were employed to analyze the data. The data validity was verified using triangulation technique. Based on the analysis, the researchers found two factors causing children to drop out of school, namely internal factors, which include a sense of laziness and lack of interest in learning; and external factors which include the low level of parental education, lack of parental attention, broken families, weak economy, and peers that have a negative influence.